ATTITUDE OF DENTAL MEDICAL WORKERS TO THEIR HEALTH - Tukhtarov Bakhrom Eshnazarovich; Valieva Markhabo Usmonovna (Western European Studies, 2024)
One of the most relevant areas of health research is the study of the patterns of its formation and attitudes towards it among various population groups. Attitude to health acts in this case as one of the essential characteristics of a healthy lifestyle [1-3]. A person’s behavior in relation to health depends on a set of motives, value orientations that influence the degree of concern for one’s health and lifestyle. On the other hand, the existing contradiction between the achievements of scientific and technological progress and the impact it has on health is expressed in a decrease in physical activity, neuropsychic overload, conflict situations, and a decrease in the body’s adaptive capabilities. All this requires a person to have a healthy lifestyle. First of all, this should be attributed to medical workers who ensure the health of the population of our Republic [4,5]. For example, as studies of the time budget of dental medical workers show, they spend much more time on medical manipulations and paperwork than is provided for in the working week: the result is overwork of the nervous system, a decrease in mental and physical performance
Keywords: Medical Workers; Dental Profile; Health